The Importance of Peer Reviewing - Jack Franklin (The Scientific World Journal)
The importance of peer reviewing articles submitted to scientific journals is a subject that conferences and journals regularly revisit. In general such visits are brief. Although a few horror stories abound: competitor holds up acceptance of paper to submit his own and so get priority or competitor pours sufficient scorn on a good paper to darken its worth.